Subconjunctival Orbital Fat Prolapse: A Case Report - Powar, Rajesh S.; M., Soujanya (Indian Journal of Plastic Surgery, 2024)
Subconjunctival orbital fat prolapse is a benign condition where the orbital fat, which normally cushions the eye within its socket, protrudes or herniates through the conjunctiva, the clear membrane covering the sclera. It is a rare condition that occurs due to disruption of the orbital septum due to various causes. In this case study, we report the clinical findings, treatment, and insights gained from the diagnosis and management of a 59-year-old male patient with subconjunctival orbital fat prolapse.
Keywords: subconjuctival; orbital; fat prolapse; conjunctiva; orbital septum